Antecedents and Consequences of Teacher Organizational and Professional Commitment - Somech, Anit; Bogler, Ronit (Educational administration quarterly, 2002)
The purpose of the present study was to examine the distinctive relationships of teacher professional and organizational commitment with participation in decision making and with organizational citizenship behavior (OCB). The data were collected through questionnaires from a sample of 983 teachers at 25 middle schools and 27 high schools in Israel. The results of the structural equation model confirmed the main hypotheses and depicted distinctive patterns of relationships regarding professional commitment and organizational commitment in schools. First, whereas participation in the managerial domain was positively associated with both the professional and the organizational commitment, participation in the technical domain was positively related with only teachers’ professional commitment. Second, professional commitment was positively associated with OCBtoward the student, whereas organizational commitment was positively associated with all three dimensions of OCB(toward the student, the team, and the organization). Implications of the study findings are discussed in relation to teachers and administrators in schools.